Exploring Mindfulness: A Comprehensive Review of Its Potential Impact on Functional Dyspepsia Management - Liman, Jakti Sugiarto; Nirmala, Putu Ayu Divya (Faculty of Medicine, Universitas Airlangga, 2025)
Introduction: This review examines the potential benefits of mindfulness-based interventions for individuals with functional dyspepsia by exploring how mindfulness practices—such as mindfulness-based cognitive therapy (MBCT), yoga, and dialectical behavior therapy (DBT)—may improve symptom relief, psychological well-being, and overall quality of life in patients suffering from this condition. By analyzing existing literature, this review highlights the promising role of mindfulness in offering a holistic approach to managing functional dyspepsia. Methods: A comprehensive literature search of related articles written in English was conducted using PubMed and Google Scholar databases, with keywords including “Mindfulness”, “Meditation”, “Yoga”, and “Functional Dyspepsia”. Results: Studies have revealed that mindfulness-based cognitive therapy (MBCT), yoga, and dialectical behavioral therapy (DBT) may reduce symptoms of functional dyspepsia and improve quality of life in patients with functional dyspepsia. Conclusion: Despite the promising findings of the initial studies, further rigorous research is needed to fully understand and confirm the effectiveness of mindfulness techniques in managing functional dyspepsia.